Schistosomiasis in School Age Children in Sierra Leone After 6 Years of Mass Drug Administration With Praziquantel - Bah, Yakuba M.; Paye, Jusufu; Bah, Mohamed S.; Conteh, Abdulai; Saffa, Sam; Tia, Alie; Sonnie, Mustapha; Veinoglou, Amy; Hodges, Mary H.; Zhang, Yaobi (Frontiers in Public Health, 2019)
Historic data and baseline surveys showed schistosomiasis as highly/moderately endemic in seven of fourteen districts in Sierra Leone, justifying annual/biennial mass drug administration (MDA) with praziquantel. MDA commenced in 2009 and reported treatment coverage had been above the World Health Organization recommended 75% of target population. Assessment in 2012 showed significant reduction in infection. In 2016, another national school-based survey was conducted to evaluate the progress. Two schools from each category (high, moderate or low) of endemic communities in each MDA district and five schools in non-MDA districts were selected. Fifty children (25 boys and 25 girls) aged 9–14 years were randomly selected per school. Parasitological examination of 1,980 stool and 1,382 urine samples were conducted. Overall S. mansoni prevalence in the seven MDA districts decreased to 20.4% (95% CI: 18.7–22.3%) in 2016 from 42.2% (95% CI: 39.8–44.5%) at baseline (p<0.0001). Mean overall S. mansoni intensity of infection reduced to 52.8 epg (95% CI: 43.2–62.4 epg) in 2016 from 100.5 epg (95% CI: 88.7–112.3 epg) at baseline (p<0.001). The prevalence of S. heamatobium in the five MDA districts that had baseline prevalence data decreased to 2.2% (95% CI: 1.5–3.1%) in 2016 from 18.3% (95% CI: 16.3–20.5%) at baseline (p<0.0001). Mean overall intensity of infection increased to 1.12 e/10ml (95% CI: 0.55–0.1.70e/10ml) in 2016 compared to 0.47 e/10ml (95% CI: 0.16–0.78 e/10ml) in 2012 (p<0.05) (no baseline data). No district was highly endemic in 2016 compared to three at baseline and there was no significant difference in prevalence or intensity of infection by sex for both species. This survey illustrated the significant progress made in controlling schistosomiasis in Sierra Leone. The fact that prevalence and intensity of infection showed an increase from the 2010 level suggested a detrimental effect of missing MDA due to the Ebola towards schistosomiasis control. The national program needs to continue the treatment and adopt a comprehensive approach including water, hygiene and sanitation measures to achieve control and elimination of schistosomiasis.